Strategi Pemerintah DKI Jakarta Dalam Implementasi Kebijakan Vaksinasi Covid-19 Tahun 2021 - Sheila WidyasMarini, (2022)
This research aims to understand the strategic used by DKI Jakarta government in overcoming high rejection and low public trust towards Covid-19. This research shows the rejection of Covid-19 vaccination in DKI Jakarta is based on religious factors, political factors, and factors regarding to the safety of the Covid-19 vaccine. This research uses qualitative descriptive method with the Head of the Epidemiology and Immunization Surveillance Section from DKI Jakarta Health Agency as main informant and The Prakarsa as secondary informant. This research is supported by the theory of Policy Implementation from Merilee S Grindle and Political Strategy from Peter Schroder. The results show that the factors of Covid-19 vaccination's rejection in DKI Jakarta can be overcome with the existing strategy, the strategy that has been established by DKI Jakarta Provincial Government and DKI Jakarta Health Agency. Therefore, this research produces good results even though Covid-19 vaccination policy in DKI Jakarta had been rejected previously. Keywords: Covid-19 vaccination, implementation, strategy, religion, politi